The Global Burden and Temporal Trends of Psoriasis, 1990–2021: Implications From the COVID‐19 Pandemic - Yunda Guo; Jie Yang; Minglu Xiao; Zhiyan Zhang; Kui Ma; Xiaobing Fu; Siming Yang (Health Science Reports, 2026)
ABSTRACT Background and Aims Psoriasis can lead to the occurrence of various chronic diseases. However, the detailed reports of psoriasis before and after COVID‐19 are limited. The present study aimed to investigate the global prevalence, incidence, and death and disability adjusted life years (DALYs) of psoriasis with age and sex differences from 1990 to 2021. Methods Data were extracted from the Global Burden of Disease (GBD) Study 2021. Our research combined multiple models such as estimated annual percentage change (EAPC), joinpoint regression (JPR), age‐period‐cohort (APC), Bayesian age‐period‐cohort (BAPC) to comprehensively and in‐depth describe the global epidemiological characteristics of psoriasis and its associations with COVID‐19 and respiratory infections. Results The ASRs of prevalence, incidence and DALYs were 516, 62, and 44.4 per 100,000 with increased change percentage, 8% (95% UI: 7.7%–8.3%), 8.8% (95% UI: 8.5%–9%) and 8% (95% UI: 7%–9%), respectively. Western Europe, Andean Latin America, and High‐income North America had highest ASRs of prevalence (1155.9, 1018.7, 975.7 per 100,000), incidence (115.3, 105, 103.5 per 100,000), and DALYs (99.8, 88.4, 83.1 per 100,000), while the most changing rate was in East Asia (30.8%, 25.6%, 31%), North Africa and Middle East (27%, 21.4%, 26.5%) and Southeast Asia (20.6%, 16.6%, 20.9%). Moreover, the annual average rate of psoriasis changed significantly before and after the COVID‐19 pandemic with different ages and sex. And the prevalence for psoriasis was negatively correlated with COVID‐19 ( R = −0.39, p < 0.001) and lower respiratory infections ( R = −0.67, p < 0.001). Finally, the trend of psoriasis will keep increasing by 2040. Conclusion The prevalence, incidence, and DALYs for psoriasis after COVID‐19 will still increase leading to a severe issue that urgently needs to be solved around world. Our present study integrated with the models and analysis will provide an important theoretical foundation for formulating measures to prevent and treat psoriasis on a global scale in the future.